Dynamics of amino acid utilization in Phaeobacter inhibens DSM 17395. Issue 18 (11th July 2013) - Zech, Hajo; Hensler, Michael; Koßmehl, Sebastian; Drüppel, Katharina; Wöhlbrand, Lars; Trautwein, Kathleen; Colby, Thomas; Schmidt, Jürgen; Reinhardt, Richard; Schmidt‐Hohagen, Kerstin; Schomburg, Dietmar; Rabus, Ralf; et al.
<x xml:space="preserve">Abstract</x> Time‐resolved utilization of multiple amino acids by Phaeobacter inhibens DSM 17395 was studied during growth with casamino acids. The 15 detected amino acids could be grouped according to depletion rate into four different categories, i.e. from rapid (category I) to nondepletion (category IV). Upon entry into stationary growth phase, amino acids of category I (e.g. glutamate) were (almost) completely depleted, while those of categories II (e.g. leucine) and III (e.g. serine) were further consumed at varying rates and to different extents. Thus, cultures entered stationary growth phase despite the ample presence of organic nutrients, i.e. under nonlimiting conditions. Integrated proteomic and metabolomic analysis identified 1747 proteins and 94 intracellular metabolites. Of these, 180 proteins and 86 metabolites displayed altered abundance levels during growth. Most strikingly, abundance and activity profiles of alanine dehydrogenase concomitantly increased with the onset of enhanced alanine utilization during transition into stationary growth phase. Most enzymes of amino acid and central metabolism, however, displayed unaltered abundances across exponential and stationary growth phases. In contrast, metabolites of the Entner–Doudoroff pathway and gluconeogenesis as well as cellular fatty acids increased markedly in abundance in early stationary growth phase.